The Ability of Women of Childbearing Age to Recognize Breast Cancer Risk Factors - Nur Asiah; M. Hanafiah; Muhammad Fidel Ganis Siregar; Teuku Tahlil (Indonesian Journal of Global Health Research, 2026)
Breast cancer is a malignancy caused by the abnormal growth and spread of cells. It develops within the breast lobules, ducts, adipose tissue, or connective tissue. Globally, this disease ranks as the second leading cause of death. Objective: This study aims to analyze the ability of women of reproductive age to recognize breast cancer risk factors. A descriptive research design was employed to identify the level of risk factor recognition among women of reproductive age in the working area of Puskesmas PB 2 Selayang. The study population comprised all women of reproductive age aged 15-49 years. A total of 100 respondents were selected using proportional random sampling, ensuring that the number of subjects drawn from each area was proportional to the population size of that area. Data were collected from April to July 2025 using a structured questionnaire administered through Google Forms, covering demographic characteristics and knowledge of breast cancer risk factors. Data collection was conducted through home visits assisted by trained enumerators. Data were analyzed using univariate analysis and presented in frequency and percentage distributions. The results indicated that the risk factors most recognized by respondents were the definition of breast cancer (74.1%), alcohol consumption habits (67%), smoking habits (71.6%), high-sugar and preservative-laden foods (75%), and breast self-examination (75%). Conversely, unrecognized risk factors included post-menopausal obesity (16.5%), early menarche (25.6%), genetic factors (56%), reproductive factors (39.4%), nulliparity (never having given birth) (52.8%), and late menopause (>50 years) (34.9%). These results suggest that a significant number of respondents lack understanding of hormonal and reproductive factors, highlighting the need for targeted education on these issues.